Response to the letter to Editor for "Bioinactivation FE: A free web application for modelling isothermal and dynamic microbial inactivation". (August 2019) - Garre, Alberto; Clemente Carazo, Marta; Fernández, Pablo S.; Lindqvist, Roland; Egea, Jose A.
Graphical abstract: Unlabelled Image